Barriers and facilitators to the implementation of individual placement and support (IPS) for patients with offending histories in the community: The United Kingdom experience. (March 2020) - Khalifa, Najat; Hadfield, Sarah; Thomson, Louise; Talbot, Emily; Bird, Yvonne; Schneider, Justine; Attfield, Julie; Völlm, Birgit; Bates, Peter; Walker, Dawn-Marie
Introduction: We aimed to identify the barriers and facilitators to the implementation of a high fidelity individual placement and support service in a community forensic mental health setting. Method: In-depth interviews were conducted with clinical staff ( n = 11), patients ( n = 3), and employers ( n = 5) to examine barriers and facilitators to implementation of a high fidelity individual placement and support service. Data was analysed using thematic analysis, and themes were mapped onto individual placement and support fidelity criteria. Results: Barriers cited included competing interests between employment support and psychological therapies, perceptions of patients' readiness for work, and concerns about the impact of returning to work on welfare benefits. Facilitators of implementation included clear communication of the benefits of individual placement and support, inter-disciplinary collaboration, and positive attitudes towards the support offered by the individual placement and support programme among stakeholders. Offences, rather than mental health history, were seen as a key issue from employers' perspectives. Employers regarded disclosure of offending or mental health history as important to developing trust and to gauging their own capacity to offer support. Conclusions: Implementation of individual placement and support in a community mental health forensic setting is complex and requires robust planning. Future studies should address the barriers identified, and adaptations to the individual placement and support model are needed to address difficulties encountered in forensic settings.